The outlook for digital technologies in military aircraft agile development - WANG Haifeng; LI Jiajun; YU Kai; CHENG Xi (Hangkong gongcheng jinzhan)
Military aircraft is characterized by outstanding comprehensive performance，considerable technical difficulties and high demand for precision and quality. With the ever-increasing requirements of military aircraft development，digital technologies have become an important means of improving the comprehensive performance，enhancing the manufacturing quality，shortening the test cycle and reducing the development cost by virtue of openness， agility and collaboration. This paper reviews the digital development history of military aircraft both at home and abroad and summarizes the digital collaborative development system features taking shape in the development of China's military aircraft represented by J-20 fighter jet. Based on the challenges presented by the future development trend of military aircraft to the existing digital technologies as well as the requirements for innovation and progress，this paper proposes a transformation from "digital" development to "agile" development and puts forward the key technologies and outlook for digital agile development of future military aircraft from the aspects of performance，manufacturing and testing.